2013
DOI: 10.1159/000351292
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Disease Burden of Hyperhidrosis in the Adult Population

Abstract: Background: Although hyperhidrosis is a common and burdensome condition, little is known about the population-based prevalence. Objective: To evaluate the epidemiology, disease burden and medical care of hyperhidrosis in German adults. Methods: Employees of fifty-two companies underwent skin screenings and interviews including hyperhidrosis questions. Results: 14,336 individuals were investigated (36% women, mean age 42 years) of whom 2,340 (16.3%) reported hyperhidrosis, including 869 (6.1%) with frequent or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 13 publications
5
74
2
7
Order By: Relevance
“…Comparable studies regarding hyperhidrosis from northern Europe are few, and factors such as research method and climate might affect the results of a population survey. The prevalence of PH (5.5%) in our study does not show the extreme variation that has been described for the disease compared to larger studies from Europe and the USA [2,5] . Similar to the mentioned studies, we are also able to describe that one quarter of those with PH have severe problems with sweating and that the prevalence of PH decreases with higher age groups while in SH it was increased.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Comparable studies regarding hyperhidrosis from northern Europe are few, and factors such as research method and climate might affect the results of a population survey. The prevalence of PH (5.5%) in our study does not show the extreme variation that has been described for the disease compared to larger studies from Europe and the USA [2,5] . Similar to the mentioned studies, we are also able to describe that one quarter of those with PH have severe problems with sweating and that the prevalence of PH decreases with higher age groups while in SH it was increased.…”
Section: Discussioncontrasting
confidence: 84%
“…In another study from Germany, where 14,336 individuals aged between 16 and 70 years were investigated, it was described that 4.6% suffered from PH and 16.3% suffered from both PH and SH [5] .…”
mentioning
confidence: 99%
“…This includes limitations in work and social relationships, physical and leisure activities, and impairments in emotional and mental health [1, 2, 4, 12, 17, 20]. The negative impact caused by excessive sweating has been reported to be similar to, if not greater than, the negative impact caused by conditions, such as psoriasis and other chronic diseases [5, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence estimates of primary (focal) hyperhidrosis outside of the United States are all higher and vary widely, ranging from 4.6 % in Germany, 5.5 % in Sweden, 12.3 % in Vancouver, Canada, 12.8 % in Japan, and 14.5 % in Shanghai, China [1, 7, 16, 20]. Prevalence estimates that include both primary and secondary hyperhidrosis range from 13.9 % in Japan, 16.3 % in Germany, 16.7 % in Vancouver, 18.4 % in Shanghai, and 20.3 % in Sweden [1, 7, 16, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent epidemiologic studies have demonstrated a greater prevalence among young, working-age individuals, who are most commonly affected and often seek healthcare professionals [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%